Progress in microencapsulation of probiotics: A review - Yao, Mingfei; Xie, Jiaojiao; Du, Hengjun; McClements, David Julian; Xiao, Hang; Li, Lanjuan (Comprehensive reviews in food science and food safety, 2020)
The potential health benefits of probiotics may not be realized because of the substantial reduction in their viability during food storage and gastrointestinal transit. Microencapsulation can be used to enhance the resistance of probiotics to unfavorable conditions. A range of oral delivery systems has been developed to increase the level of probiotics reaching the colon including embedding and coating systems. This review introduces emerging strategies for the microencapsulation of probiotics and highlights the key mechanisms of their stress–tolerance properties. Recent in vitro and in vivo models for evaluation of the efficiency of probiotic delivery systems are also reviewed. Encapsulation technologies are required to maintain the viability of probiotics during storage and within the human gut so as to increase their ability to colonize the colon. These technologies work by protecting the probiotics from harsh environmental conditions, as well as increasing their mucoadhesive properties. Typically, the probiotics are either embedded inside or coated with food‐grade materials such as biopolymers or lipids. In some cases, additional components may be coencapsulated to enhance their viability such as nutrients or protective agents. The importance of having suitable in vitro and in vivo models to evaluate the efficiency of probiotic delivery systems is also emphasized.